KESAN PETUNJUK STRUKTUR DAN KONTEKS DALAM RESOLUSI KETAKSAAN KATA GANTI NAMA DIRI KETIGA DALAM KALANGAN PENUTUR MELAYU - Nurul Aqilah Nabihah, Khairil Anuar (Universiti Malaysia Sarawak, (UNIMAS), 2025)
This study investigates how native Malay speakers interpret the referent of the third-person pronoun dia in contexts of ambiguity. The research focuses on two primary objectives: identifying whether there is a default preference for the subject as referent, and evaluating the influence of contextual discourse cues on pronominal reference resolution. A total of 60 adult native Malay speakers participated in a comprehension task involving ambiguous sentences presented in three contextual conditions: neutral, subject-biased, and non-subject-biased. Data were analysed using a generalised mixed effects model (GLMM) implemented in R. Findings reveal a significant overall preference for the subject as referent across all conditions, supporting the existence of a default syntactic strategy. However, contextual effects revealed unexpected patterns: neutral contexts enhanced subject preference, subject-biased contexts paradoxically reduced it, and non-subject-biased contexts had no significant effect. These results challenge the predictions of the Referential Context Theory and suggest that pronominal processing in Malay is shaped by linguistic features such as the absence of gender marking and syntactic flexibility. The study highlights the need for reference resolution models that account for cross-linguistic variability